IMPROVING STUDENTS’ SPEAKING SKILLS THROUGH TIME TOKEN ARENDS TECHNIQUE - Khairun Ihsani Harahap; Nova Andriani (Journal MELT (Medium for English Language Teaching), 2021)
This research was aimed at improving at the tenth grade students' speaking skills through Time Token Arends Technique using recount texts at SMA Negeri 3 Medan. This research was classified as a Classroom Action Research (CAR). The implementation is carried out in two cycles, each of which consists of four stages, namely planning, implementing the action, observing, and reflecting. The data were collected from spoken test, observation, and document. The observation during the process of English teaching and learning was conducted by the observer. In this research the researcher took 21 students of one excellent class. Then, the researcher gave pre-test and post-test. The results of the research show that the action on improving students’ speaking skill through Time Token Arends Technique using recount texts is successful. After doing the research, the researcher got the data both from pre-test, post-test 1 and post-test 2. The research findings showed: The results of average of pretest score was 52,14 meanwhile the minimal mastery criterion (Kriteria Ketuntasan Minimal/ KKM) is 75. This means, only 14.28% of students pass the KKM. Furthermore, the mean posttest 1 and posttest 2 scores were 71.42 and 82.61. The results showed that the percentage of students who scored above the KKM was 95%. Based upon the finding of the data above the researcher concluded that using time token arends increase students’ speaking skills.